The Nexus of Knowledge Management and Partnership Network in Nurturing the Business Continuity of Agro-Industry - Iwan Hermawan; Gita Hindrawati; Yusuf Dewantoro Herlambang; Inayah Inayah; Lusiana Rahmawati (Research Synergy Foundation, 2024)
This study aims to find the best model for coffee agribusiness development in Indonesia that acquires the construct of knowledge management. Knowledge Management helps businesses effectively collect, store, and use relevant information. The effectiveness of such information management is becoming increasingly important despite complex challenges such as intense competition and changing economic conditions. The main problem is that contradictions result in the relevance relevance between Knowledge Management and Business Continuity. From these problems, this research offers the Partnership Network as a mediating variable. This study aims to empirically examine the effect of knowledge management on business continuity. This research offers the Partnership Network variable as a mediator from the perspective of Resource-Based View Theory and Knowledge-Based View Theory. This study employs a quantitative approach with a positivism paradigm. The number of samples in this study was 179 with data testing using Structural Equation Modeling (SEM) with the SmartPLS analysis tool. This study found the effect of Partnership Network (PN) mediating variables that bridged Knowledge Management (KM) to Business Continuity (BC), namely Internalization (IN) to Business Continuity (BC), by 0.130. The perspective of this study uses the Resource Based View Theory and Knowledge-Based View Theory. Coffee farm owners need to join a trusted certified community to receive active knowledge transfer. The knowledge gained from training must be immediately applied to managing coffee farm challenges, such as lack of fertilizer and changing soil characteristics.